PENGARUH VARIASI JARAK ELEKTRODA TERHADAP UNJUK KERJA ELEKTROLISER TIPE WET CELL - Muhaammad Naufal Harist; Moch. Dhofir; Eka Maulana (Jurnal Mahasiswa TEUB, 2022)
This study discusses how to reproduce HHO (Hydrogen Hydrogen Oxygen) gas by water electrolysis process with electrolyzer wet cell or wet type. The method used in this research is experimental. The design of this tool is divided into 3 main stages, manufacture of containers, manufacture of water traps, and manufacture of gas flowmeters. The container measuring 120 mm x 100 mm x 140 serves as a place for the process of separating water molecules (?2?) into its constituent compounds, namely hydrogen (?2 ) and oxygen (?2 ) or it can be called water electrolysis. The electrode used is a graphite with measuring of graphite electrode is 140 mm x 20 mm x 20 mm. 20 grams of Potassium hydroxide (KOH) serves as a catalyst to help accelerate the process of separating water molecules in electrolysis. The container will be connected to a water trap and then a gas flowmeter or gas measuring instrument. This study shows that designing a wet type HHO gas generator with a pure DC source and a PWM source will have a correlation between HHO gas production and variations of the distance between two electrodes. At a distance of 2 cm the electrode produces HHO gas of >1200 ml with a pure DC source within 15 minutes. For an electrode distance of 4 cm the HHO gas produced is 1200 ml with a pure DC source within 15 minutes. And for an electrode distance of 6 cm the HHO gas produced is 880 ml with a pure DC source within 15 minutes. Meanwhile, at a distance of 2 cm from the electrode with a PWM source of HHO gas, the resulting HHO gas is >1200 ml in 15 minutes. For an electrode distance of 4 cm with a PWM source of HHO gas, 1030 ml is produced in 15 minutes. And for the electrode distance of 6 cm with a PWM source of HHO gas, 690 ml is produced in 15 minutes.Keywords: electrolyzer wet cell, HHO gas, distance of electrodes